Sistem Perencanaan Strategi Menggunakan FQSPM - Fera Tri Wulandari (Universitas Boyolali, 2022)
The strategic planning system uses Fuzzy Quantitive Strategic Planning Matrix (FQSPM) to help create strategies based on the results of internal and external analysis of the organization and uses Fuzzy TOPSIS for the process of determining the selected strategy that will be implemented in the organization. The information generated from the strategic planning system can be used by the organization in anticipating changes in the external environment so that the organization can formulate where the organization will be directed, and how resources are allocated to achieve goals over a certain period of time and in various possibilities.